Pengaruh Metode Group Investigation terhadap Hasil Belajar Siswa pada Muatan Materi PPKn di Kelas V SDN 2 Kalijaga - Zuhdi, Ferianto; Khairunnisa, Khairunnisa; Syahrul Jiwandono, Ilham (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
One of the factors that impact the unsuccessfulness of studying PPKn in schools is the use of a learning model that is still less innovative. Teachers tend to use the old method that is teaching the materials using lectures, questions and answers, then giving the student assignments. As a result, students feel bored, passive, less interested in learning, which decrease students’ learning outcomes. Group Investigation can be used as an alternative that will encourage students to be more active in learning with groups. This study aims to determine the effect of Group Investigation on students’ learning outcomes in studying PPKn in the fifth grade student at SDN 2 Kalijaga academic year 2020/2021. This research is experimental research with Quasi Experimental Design type Nonequivalent Control Group Design. Population of this research was the fifth grade students of SDN 2 Kalijaga in academic year 2020/2021 consisting of two classes. The total number of the population was 45 people, all of them were chosen as the sample, where V/A as the experimental class and V/B as the control class. The researcher conducted observation and test to collect the required data. The result from the observation of applying Group Investigation in teaching indicate